Unveiling the academic, sociocultural, and psychological adaptation challenges of Chinese international students in Malaysia: A systematic review - Xue, Wenou; Kaur Mehar Singh, Manjet (Journal of International Students, 2025)
This systematic review explores the academic, sociocultural, and psychological adaptation challenges encountered by Chinese international students in Malaysian higher education institutions, synthesizing findings from 24 peer-reviewed studies published between 2010 and 2024. It highlights Malaysia’s distinct adaptation context, characterized by unique language barriers within an English–medium instruction (EMI) setting, cultural and religious differences, and specific social integration challenges. This review offers new insights into the adaptation process of Chinese students by framing these challenges within Malaysia’s multicultural, predominantly Islamic environment, which presents unique dynamics compared with Western educational contexts. The findings also reveal research gaps and offer recommendations for institutional policies to enhance the adaptation experience of Chinese students in Malaysia.